2018
DOI: 10.1002/erv.2581
|View full text |Cite
|
Sign up to set email alerts
|

Blunted cortisol response to stress in patients with eating disorders: Its association to bulimic features

Abstract: The results support the association between blunted cortisol response and bulimic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…It was also shown in outpatients with AN and BN with an average BMI in the normal range that heightened TSST-induced cortisol secretion is associated with high attachment anxiety or avoidance which might result from childhood trauma (35). Vaz-Leal et al (36) demonstrated also blunted cortisol stress responses to the TSST in patients with AN and BN (considered as a single group in contrast to HCs) which is in line with our findings. Additionally, they showed that this blunted cortisol response pattern is mainly associated with binge-purging eating behavior as seen typically in BN but sometimes in AN as well.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also shown in outpatients with AN and BN with an average BMI in the normal range that heightened TSST-induced cortisol secretion is associated with high attachment anxiety or avoidance which might result from childhood trauma (35). Vaz-Leal et al (36) demonstrated also blunted cortisol stress responses to the TSST in patients with AN and BN (considered as a single group in contrast to HCs) which is in line with our findings. Additionally, they showed that this blunted cortisol response pattern is mainly associated with binge-purging eating behavior as seen typically in BN but sometimes in AN as well.…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous observations (19,36) we predicted that patients with EDs will show blunted cortisol stress responses at pre-treatment compared to HCs. As described before (19) we suppose a long-term exhaustion of the HPA axis in patients with ED that makes individuals vulnerable for this and other psychological disorders.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies point to a possible decrease in baseline cortisol levels and cortisol awakening response (e.g. Rosenberg et al, 2013;Vaz-Leal et al, 2018), but overall there is more support for increased levels, at least in BN (e.g. Monteleone et al, 2017;see Culbert et al, 2016 for an overview).…”
Section: Negative Affect and Stressmentioning
confidence: 99%
“…Whether this is also the case for BED is debatable, since the number of studies is more limited. The majority of studies report a blunted response in BN and BED following acute stress (Carnell et al, 2018;Culbert et al, 2016;Ginty et al, 2012;Het et al, 2015b;Koo-Loeb et al, 1998;Naish et al, 2018;Rosenberg et al, 2013;Vaz-Leal et al, 2018;Wierenga et al, 2018), but not all do (Coutinho et al, 2007;Vannucci et al, 2015). This blunted reactivity is also positively associated with binge-eating severity in BED (Coutinho et al, 2007) and an increase in the desire to eat after acute stress exposure (Rosenberg et al, 2013).…”
Section: Negative Affect and Stressmentioning
confidence: 99%